Perlindungan Hak Cipta Karya Seni Lukisan Terhadap Plagiarisme Yang Menggunakan Artificial Inteligence - I Made Budiana; Ni Made Jaya Senastri; I B Gd Agustya Mahaputra (Fakultas Hukum Universitas Ngurah Rai, 2026)
The progression of Artificial Intelligence (AI) technology presents new challenges in copyright protection, particularly regarding paintings that possess the unique characteristics and styles of their creators. The ability of AI to generate visual works through data scraping processes sourced from the internet potentially leads to acts of plagiarism, affecting both visual expressions and specific artistic styles. This study aims to analyze copyright regulations concerning paintings under Law Number 28 of 2014 on Copyright and to review the form of legal protection for creators against AI-driven plagiarism. This study applies a normative legal research method with a statutory and conceptual approach, supported by primary and secondary legal materials. The effect indicate that copyright protection for paintings is established through Moral Rights and Economic Rights, which arise automatically based on the declarative principle. However, specific regulations regarding AI-based plagiarism do not yet exist, resulting in losses for artists. Therefore, regulatory updates are necessary to adapt to these changes, ensuring legal certainty and optimal protection for creators in the digital era.